Calorimetric elucidation of ionic interactions in room temperature ionic liquid solutions - Rai, Gitanjali; Kumar, Anil (Clean Technologies and Environmental Policy, 2014)
Knowledge of thermal properties of room temperature ionic liquid (RTIL) solutions is essential in chemical process designing in addition to their application in understanding ionic interactions at molecular level. RTILs are considered to be substitutes for volatile organic compounds. While some experimental thermal data on these systems are available in a random manner, the modeling efforts to correlate enthalpy-concentration profiles of RTIL solutions are very scanty. In this review, an effort has been made to compare and discuss the experimental data of these RTIL solutions available in the literature. The readers are also made aware of the disappointing situation regarding the availability of any type of correlative models for the enthalpy-concentration data of the RTIL systems. An accurate knowledge of activity coefficients at infinite dilutions, Iyen (i) (a) acquired from thermal data will serve as inputs for the newer less polluting process designing and thus open opportunity for a cleaner environment.
Keywords: Calorimeters; Correlative models; Excess partial molar enthalpy; Room temperature ionic liquids